VIDEO GAME SEBAGAI MEDIA PEMBELAJARAN SEJARAH (Suatu Alternatif dalam Menyelenggarakan Pembelajaran Sejarah) - Johan Wahyudhi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2014)
This article describes an alternative teaching history, namely through the application of learning media in the history of video games. Education history is a lesson that can be used as a vehicle for the formation of character among the younger generation, among others by promoting the values of patriotism, nationalism civic, virtues, and human values. However, today the teaching of history has not gone well as expected. Learning history is often monotonous and boring for students. In this case, the video game is an alternative to get out of problems in learning the history. Video games are popular entertainment media in the lives of children that can be used as a medium of teaching history in a creative, fun, and effective way.